Klasifikasi Kain Tenun Kolana Berdasarkan Motif Warna Dan Keberagaman - Loban, Jeni Marianti; Ena, Maktisen; Molebila, Didiana Yanuarita (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The Kolana community in Alor Regency, East Nusa Tenggara has a social system that is still maintained today, this is marked by the existence of the king as the highest leader in the traditional structure and tribal chiefs. Each tribe has a tribal chief, each tribe consists of tribal members, namely families with certain clans. Woven cloth is one of the most important traditional objects and must be used in every traditional procession or ritual such as marriage proposals, traditional fines, until death. Each tribe has its own woven cloth with its name, motif, color and meaning. As time goes by, sacred values ​​and cultural values ​​slowly begin to shift due to various factors. This service activity aims to document traditional objects which are an inseparable part of the socio-cultural life of the people of Alor Regency, especially the Kolana people. The result of this service activity is documentation of the classification of kolana woven cloth based on name, ownership, motif and diversity.